FACE WORK SEORANG SPY DALAM GAME ONLINE SUPER ARMADA - Saptiyono, Ami (Interaksi: Jurnal Ilmu Komunikasi, 2016)
AbstractOnline media is media that provides a variety of facilities and services for people in activities and meet their needs. This media allows everyone to do variousÂ  activities such as browsing , blogging , chat , update your status, upload and download data, and even play games . In this article , the researcher discuss how an online game players do face work in the activities of online gaming , especially in the game "Super Armada" , through autoethnography methods , as a method of doing descriptions experience of researcher in this online game , using face work theory as reference in researchKey words: Face work, Autoethnography, Media online.